The East–West Divide in Response to COVID-19 - Jamison, Dean T. (Engineering (Beijing), 2021)
Coronavirus disease 2019 (COVID-19) deaths per million population in the countries of the West had often exceeded those in the countries of the East by factor of 100 by May 2021. In this paper, we refer to the West as represented by the United States plus the five most populous countries of Western Europe (France, Germany, Italy, Spain, and the United Kingdom), and the East as the 15 countries in East Asia and Oceania that are members of the Regional Comprehensive Economic Partnership, RCEP (Australia, Brunei, Cambodia, China, Indonesia, Japan, the Republic of Korea, Laos, Malaysia, Myanmar, New Zealand, Philippines, Singapore, Thailand, and Vietnam). This paper argues that currently available information points to the factors most responsible for the East–West divide. Warnings by early January 2020 about an atypical viral pneumonia in Wuhan, China, prompted rapid responses in many jurisdictions in East Asia. Publication of the virus’s genome on 10 January 2020 provided essential information for making diagnostic tests and launching vaccine development. China’s lockdown of Wuhan on 23 January 2020 provided a final, decisive signal of the danger of the new disease. By late March 2020, China had fully controlled its epidemic, and many other RCEP countries had taken early and decisive measures, including restrictions on travel, that aborted serious outcomes. Inaction during the critical month of February 2020 in the United States and most other Western countries allowed the disease to take hold and spread. In both the East and the West, stringent population-wide non-pharmaceutical interventions were widely implemented at great cost to societies, economies, and school systems. Without these measures, the outcomes could have been even worse. Most countries in the East also implemented tightly focused policies to isolate infectious individuals. Even today, most countries in the West allow infectious individuals to mingle with their families, coworkers, and communities. Much of the East–West divide plausibly results from failure in the West to implement the basic public health policies of early action and the isolation of infectious individuals. Widespread immunization in some RCEP and high-income countries will soon attenuate their outbreaks, while the slow rollout of vaccines in lower income countries is replacing the East–West divide in outcomes with a North–South one. The South is thus replacing the West as the breeding ground for more dangerous variants as exemplified by the highly contagious Delta variant, which may undermine hitherto successful control strategies in many countries.